Powers of Interest Groups and Policy Processes - Srichan, Thanikarn; Pho Singh, Phakdee (Journal of Modern Learning Development, 2023)
This article focuses on the power, Interest groups, and policy processes consist of powers, interest groups, and policy processes. The group of people with power, Power (Power) refers to the ability of a person to make another person act according to what that person wants. The power called (Authority) power to command by allowing others to perform their duties as required by law, group of people with benefits, group of people who are characterized by an agglomeration with purpose and same interests do activities together. The other is that a person or group of people who come together to seek or influence on public policy, Policy processes: Policy formation, Policy formulation, Policy decision, Policy Implementation, and Policy evaluation. Including continuation, substitution, termination of a policy. From the process of public policy from the inception of the policy to the end of the policy. This requires a person with authority to act as an operator in each policy process. In the policy process, there may be stakeholders other than those directly authorized to act. Which leads to hidden benefits of government agencies and interest groups affecting the implementation of the policy process in each step of the policy process. Which has the effect of creating a policy or not creating a policy.